Natural resource conservation and management in the Sierra Nevada of Santa Marta : case study (2005)
The Sierra Nevada of Santa Marta of Colombia is a region of immense cultural, historical, ecological and biological value. However, external interventions have caused serious cultural, social and environmental damage. This case study illustrates how the development of a constitutional, legal and policy framework, which recognized the cultural and territorial rights of the indigenous communities of the Sierra Nevada, facilitated the building of coordination mechanisms for the design of conservation strategies. It also shows how there still are important challenges to secure the effectiveness and equity of these strategies. Following the analytical framework of the World Development Report (WDR) 2003 , this case study analyzes how society and institutions became aware of the values and problems of the Sierra Nevada of Santa Marta, the mechanisms that have generated decisions to undertake action, the mechanisms which have been in place to balance legitimate and competing social interests, and the means by which the adopted solutions have been executed. Finally, this document presents some lessons and recommendations.